Enhancing students reading comprehension through student - student cooperation extensive reading : - Nguyễn, Thị Kim Thanh (Can Tho University, 2008)
This study examines the effects of student - student cooperation extensive reading. The purpose of this experimental study was to investigate whether encouraging student - student cooperation extensive reading helps improve students' reading comprehension.